Diverse Fab specific for acetylcholine receptor epitopes from a myasthenia gravis thymus combinatorial library. - Farrar, J; Portolano, S; Willcox, N; Vincent, A; Jacobson, L; Newsom-Davis, J; Rapoport, B; McLachlan, S (1997)
The muscle weakness in myasthenia gravis (MG) is caused by heterogeneous high-affinity IgG autoantibodies to the nicotinic acetylcholine receptor (AChR), a complex ion channel glycoprotein. These antibodies are clearly responsible for reducing AChR numbers at the neuromuscular junction in myasthenia; however, the origins, diversity, specificity and pathogenicity of individual antibodies have not yet been established. We have cloned and characterized four different AChR-specific Fab from an MG patient's thymus by screening an IgG1/kappa gene combinatorial lambda phage library with soluble human AChR labeled with [125I] alpha-bungarotoxin. Unlike most previously cloned human antibodies, all four Fab immunoprecipitated soluble human muscle AChR. Two Fab strongly inhibited binding of mAb to the main immunogenic region on the alpha subunits and one Fab bound to an epitope on the fetal-specific gamma subunit. In sensitivity and fine specificity, these Fab resembled the anti-AChR antibodies found in many MG patients, including the donor. The closest germline counterparts for their heavy chains were in VH families 1, 3 and 4; however, there were many differences consistent with an antigen-driven response of diverse B cell clones. The combinatorial approach holds promise for further analysis of human autoantibodies.